The Application Activity Based Costing (ABC) As the Basis for Determining Inpatient Rates at The Al-Aziz Hospital in Jombang - Suud Al Habsyi (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
The purpose of this study is: (1) to give an idea how the determination rates of hospitalization in AL-AZIZ hospital by using the method of Activity-Based Costing (ABC). (2) to know the comparison rates of hospitalization services based on calculations done by AL-AZIZ hospital management with a calculation based on the method of Activity-Based Costing (ABC). Informants in this study are a part of the accounting employees who are empowered to provide information to researchers. Data collection techniques used namely directional interview and documentation. The results of calculations using the ABC method give the calculation result is lower compared with that determined by the management of AL-AZIZ hospital in the VIP class and class I, as well as the calculation result is higher in class II and class III. The difference for each of VIP class, class I, class II, and class III Rp 17,764.02, Rp 17,434.25, (Rp 20,762.65), and (Rp 11,908.99).